(untitled) (Research, Society and Development, 2022)
Objective: To build an institutional communication tool a powerful management tool that, being strategically used, can act in a way that internalizes the goals, values, mission and vision of the institution. Methodology: This is a methodological development study conducted with the workers of SAMU 192 Ceará. The construction of this tool occurred through the search in the scientific literature through an integrative review. The application of a questionnaire with sociodemographic characteristic was also used. Then there was the validation of the content of the tool with specialists and usability validation with the workers of SAMU 192 Ceará. Results and Discussion: This tool passed through the validation of judges/specialists, and it presented significant CVI (0.88 value higher than the minimum required), as well as SUS score (higher than 70, in this case 71.5) revealing the applicability of fanpage to the workers of samu 192 CE. Conclusion: It is expected that this tool can help improve communication, promoting greater integration between managers and workers and favor the dissemination and internalization of goals and values, as well as the mission and vision of the institution.